2019
DOI: 10.3390/ma12233931
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength and Dispersibility of Pulp/Danufil Wet-Laid Hydroentangled Nonwovens

Abstract: Wet-laid hydroentangled nonwovens are widely used for disposable products, but these products generally do not have good dispersibility and can block sewage systems after being discarded into toilets. In this study, both pulp fibers and Danufil fibers are selected as we hypothesize that the high wet strength and striated surface of Danufil fibers would allow us to produce nonwovens with better dispersibility while having enough mechanical properties. The wet strength and dispersibility of nonwovens are systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…This is ascribed to the microstructure of the studied samples. The cellulose fibers become intensely entangled during the spun-lacing step in their manufacturing, due to mechanical agitations through high-pressure water jets. , During the paper suspension-making process, the cellulose fibers are separated by solvent molecules. Upon draining the solvent, the separation between the cellulose fibers is alleviated yet insufficient to bring the fibers to their original structure, as is the case in the cellulose paper.…”
Section: Resultsmentioning
confidence: 99%
“…This is ascribed to the microstructure of the studied samples. The cellulose fibers become intensely entangled during the spun-lacing step in their manufacturing, due to mechanical agitations through high-pressure water jets. , During the paper suspension-making process, the cellulose fibers are separated by solvent molecules. Upon draining the solvent, the separation between the cellulose fibers is alleviated yet insufficient to bring the fibers to their original structure, as is the case in the cellulose paper.…”
Section: Resultsmentioning
confidence: 99%
“…Pristine cellulose nonwovens (CNWs) with excellent breathability and biodegradability, were prepared by wet-laid formation followed by hydroentanglement consolidation as described previously [33] , [34] , in which 20 wt% bleached softwood pulp (fiber length of 2.4-2.6 mm, width of 34.7 ± 9.2 µm, and thickness of and 5.0 ± 1.8 µm) and 80 wt% Lyocell fibers (fiber length of 12 mm, diameter of 11.9 ± 1.1 µm) were homogeneously mixed in a fiber mixing chest. The mixed fiber slurry was pumped to a hydroformer to form the wet-laid fiber web which was consolidated by water jets to obtain the CNWs.…”
Section: Methodsmentioning
confidence: 99%
“…These types of wet wipes are usually manufactured from hydroentangled wetlaid nonwovens 2,3 treated with water-based lotions. 4 Hydroentangled, wetlaid nonwovens as a precursor of wet wipes consist of man-made cellulose fibres (MMCF), e.g., viscose fibres, 5 lyocell fibres, 6 but also non-cellulosic synthetic fibres and short wood pulp fibres. The wetlaid process allows the usage of short wood pulp fibres and long viscose fibres in a compound, both being cellulosic and biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work it was demonstrated that pilot-scale produced wet wipes deteriorate in their dispersibility during wet storage and the effect was named dispersibility ageing. 23 With this effect, it is possible to explain why never-wetted, dry nonwovens disperse well 5,6,10 and wet stored wet wipes do not. 11,12 The underlying mechanisms of dispersibility ageing are still not understood.…”
Section: Introductionmentioning
confidence: 99%